TAKING ANALOGY SERIOUSLY: STATUTORY ANALOGY IN CREATION AND INTERPRETATION OF LAW - Dajović, Goran (Pravni zapisi, 2020)
In the article, author analyzes analogy generally and analogy in law, as a way of reasoning. The traditional division of the application of analogy in law into analogia legis and analogia iuris is perceived as incomplete and insufficiently clarifying for what is really happening in the practice of law. Instead, as a starting point, it emphasizes the division of analogies in law into casuistic and statutory analogy. While in common law systems the former is more applied and studied, in continental legal systems, due to the primacy of written sources of law, it is more interesting to consider the latter. The statutory analogy is firstly analyzed from the aspect of its form and content (retrieval and mapping). After that, its basic types are described. The first is the analogy extra legem, which serves to fill legal gaps, or more precisely, which attributes legal consequences to facts that are not explicitly described in the applicable legal provision. The second type of statutory analogy is analogy intra legem, in which the argument of analogy is used to interpret legal norms. In the article are particularly depicted the two “incarnations” of analogy intra legem, extensive interpretation and systemic interpretative argument of analogy. Finally, through several cases from judicial practice of Serbian courts, it is illustrated how the statutory analogy is applied in this practice only intuitively, and therefore insufficiently explained, and, after all, incorrect.
Keywords: Statutory analogy; analogy extra and intra legem; retreival; mapping; interpretation of law